Experimenteller Umgang mit Spiegelung und Perspektive unter Verwendung von Dynamischer Geometriesoftware (mathematica didactica, 2003)
This paper shows an approach to combine real operations in front of a mirror with perspective drawings in Dynamic Geometry Software. In  a neurophysiological view on the  spatial sense the relationship between real-life  objects in front of a mirror  and geometrical  constructions in the software are of fundamental importance for the association of geometrical representations of 3D-space and perspective drawings.